Reading and Writing from Literature - Schwiebert, John E. (Boston Houghton Mifflin Company, 1997)
Designed for use in literature courses that are also writing courses. It offers a fresh new approach to reading and writing. The book invokes a "conversation" model of reading and writing that empowers students to interact proactively and constructively with all texts, both literary and their own.
Keywords: Literature